A comparison between alternating segment Crank-Nicolson and explicit-implicit schemes for the dispersive equation. (1st January 2014) - Haghighi, Ahmad Reza; Shahbazi Asl, Mohammad
In this paper, the alternating segment Crank-Nicolson (nASCN) scheme is compared to the alternating group explicit-implicit (nAGEI) scheme for the dispersive equation with periodic boundary conditions. Both schemes are unconditionally stable and have a truncation error of the fourth-order in space. The comparison between the accuracy of these two schemes is presented in the numerical experiments.